BDNF and Netrin-1 repression by C/EBPβ in the gut triggers Parkinson's disease pathologies, associated with constipation and motor dysfunctions. (March 2021) - Ahn, Eun Hee; Kang, Seong Su; Liu, Xia; Cao, Xuebing; Choi, Soo Young; Musazzi, Laura; Mehlen, Patrick; Ye, Keqiang
Highlights: Parkinson's disease patients display decreased BDNF and netrin-1 in the gastrointestinal (GI) tract, associated with TH-positive neuronal loss and Lewy body-like inclusions. p-C/EBPβ inversely correlates with BDNF and netrin-1 levels in dopaminergic neurons in the gut and the brain. C/EBPβ binds the promoters and is a transcription repressor for both BDNF and netrin-1. Gut conditional knockout of BDNF and netrin-1 elicits PD non-motor, Lewy body-like pathologies and motor symptoms in SNCA PD mouse model. Abstract: Chronic constipation is one of the most prominent prodromal symptoms in Parkinson's disease (PD), and Lewy bodies, enriched with aggregated α-Synuclein (α-Syn), propagation from the gut into the brain has been proposed to play a key role in PD etiopathogenesis. BDNF (Brain-derived neurotrophic factor) and Netrin-1 promote both neuronal survival and regulate the gut functions. We hypothesize that C/EBPβ represses BDNF and Netrin-1 in peripheral nervous system and central nervous system, contributing to GI tract and brain malfunctions in PD. To test the hypothesis, we performed the studies in both human PD gut tissues and BDNF or Netrin-1 gut conditional KO mice models. Lewy bodies with α-Syn aggregation and neuro-inflammation were measured in the colon and brain samples from PD patients and healthy controls and rotenone or vehicle-treated WT and CEBPβ (+/-) mice. We show that both BDNF and Netrin-1 are strongly decreased in the brain and the gut of PD patients, and conditional KO of these trophic factors in the gut elicits dopaminergic neuronal loss, constipation and motor dysfunctions. Interestingly, the inflammation and oxidative stress-induced transcription factor C/EBPβ acts as a robust repressor for both BDNF and Netrin-1 and suppresses the expression of trophic factors, and its levels inversely correlate with BDNF and Netrin-1 in PD patients. Our findings support that gut inflammation induces C/EBPβ activation that leads to both BDNF and Netrin-1 reduction and triggers PD non-motor and motor symptoms. Possibly, C/EBPβ-mediated biological events might be early diagnostic biomarkers for PD.